Xylanases of Trichoderma koningii and Trichoderma pseudokoningii: Production, characterization and application as additives in the digestibility of forage for cattle. (September 2022) - Sanguine, Isadora Stranieri; Cavalheiro, Gabriela Finoto; Garcia, Nayara Fernanda Lisboa; Santos, Mariana Viegas dos; Gandra, Jefferson Rodrigues; Goes, Rafael Henrique de Tonissi e Buschinelli de; Paz, Marcelo Fossa da; Fonseca, Gustavo Graciano; Leite, Rodrigo Simões Ribeiro
Abstract: The work optimized the production of xylanases by solid-state cultivation by Trichoderma koningii and Trichoderma pseudokoningii . The xylanases were biochemically characterized, the catalytic potential of enzymatic extracts and their use as an additive in the feeding of ruminants were evaluated. The higher production of xylanases by T. koningii, approximately 524.3 U g −1 (or 52.43 UmL −1 ), was obtained for cultivation in a substrate composed of wheat bran and sugarcane bagasse in a 4:1 g ratio, respectively, containing 60% initial moisture, and kept at 20 °C for 120 h. The xylanase used by T. koningii showed excellent activity at pH 4.5 and 50 °C and remained stable at pH 3.0–9.5 and for 1 h at 45 °C. T. pseudokoningii had a higher production of xylanase, 721.0 U g −1 (72.10 UmL −1 ), when grown in wheat bran, with 50% initial moisture, at 25 °C for 96 h. The xylanases produced by T. pseudokoningii showed greater catalytic activity at pH 4.5 and 55 °C and were stable at pH 3.0–9.5 and for 1 h at 50 °C. The best results of in vitro digestibility were obtained in Mombaça grass containing the enzymatic extract of T. koningii, reaching a maximum gain of 12% in digestibility, expressed in dry mass. The chromatographic profile of the products resulting from the enzymatic hydrolysis of xylan indicated the predominant action of endoxylanases. Additionally, the enzymatic extracts showed reduced cellulolytic activity, which enables its use in cellulose pulp bio-bleaching processes. Highlights: Xylanase production by Trichoderma koningii and Trichoderma pseudokoningii . Enzymes produced in low-cost media: wheat bran and sugar cane bagasse. Enzymatic extracts with reduced cellulolytic activity. Potential for application of enzymes as digestive additives in cattle diet.